Subversion of the complement system by viruses - Sahu, Arvind (Henry Stewart Talks, 2018)
Recognition of viruses by the complement system, Role of complement in antiviral immunity, Complement subversion by viruses: molecular mimicry, molecular piracy, use of complement receptors and regulators for cellular entry, and modulation of complement protein expression